Prevalence of hepatitis B and C virus infections among military personnel - Villar, Livia M. (2015)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Hepatites Virais. Rio de Janeiro, RJ, Brasil.